New technique for treatment of postcatheterization radial artery pseudoaneurysm. Issue 3 (16th August 2016) - Babunashvili, Avtandil M.; Pancholy, Samir B.; Kartashov, Dmitriy S.
Abstract : We report a new technique for treatment of radial artery pseudoaneurysm (RAP) caused by transradial access (TRA) for coronary angiography. Traditional extrinsic compression with radial flow cessation leads to a local milieu likely associated with an increase in probability of radial artery occlusion (RAO). Our technique involves obtaining ipsilateral radial artery access distal to the neck of the RAP followed by a prolonged sheath dwell time covering the neck of the RAP which allows the RAP sac to thrombose and maintains radial artery lumen patency. © 2016 The Authors. Catheterization and Cardiovascular Interventions Published by Wiley Periodicals, Inc.